(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
An Islamic revival and reform movement led by Md. Ibn Abd al-Wahhab emerged in Saudi Arabia in the 18th century, which came to be known as Wahabbi movement. It was a puritanical movement which advocated the adherents of the faith to strictly follow the Islamic doctrines and teachings enshrined in the Quran, hadith (words or actions of Prophet Muhammad) and the shariat (Islamic law), and purge the un-Islamic beliefs and practices. The movement inspired many religious leaders in various parts of the Muslim world to initiate similar puritanical movements in their own lands. In South Asia too, several revivalist movements emerged. Eastern India, particularly undivided Bengal, became the nerve centre of these movements. From Bengal the movement reached its influence among the Bengali speaking Muslims in Southern parts of Assam, and further to the Muslims in Manipur, a small state in the easternmost part of South Asia. Manipuri Muslims, who were taking refuge in Barak Valley during the Burmese occupation of Manipur from 1819 to 1826, were introduced to Islamic knowledge and learning. After their return to Manipur, a handful of Muslims began to revitalize the faith of the ordinary Muslims through preaching. In the 20th century, the Islamic scholars trained and educated in the madrassas outside Manipur and Tablighi Jamaat carried the revival movement forward. These movements greatly helped in reforming and revitalizing the religious life of the Muslims in Manipur. This research paper is an attempt to trace the growth of the Islamic revival and reform movement in South Asia with special reference to Manipur, taking into account the ideology, nature, course and the outcomes of the movements.